Achieving a wider audience in museums using modern technologies - Teyyubova, Khadija; Bashirli, Mahbuba; Ahmadova, Salima (ADA University, 2023)
Low attendance rate is one of the important issues that many museums face. This capstone project aims at investigating low attendance issue in museums of Azerbaijan and addressing it through the use of modern technology. The study has revealed that the low attendance issue remains untapped due to lack of awareness on exhibitions, activities, limited digital accessibility of museums, and disinterest in history and culture. The study offers policy solutions for each of these challenges - increasing social media engagement, creating, implementing digital platforms, applications and increasing the number of thematic and interactive museums or expositions. All these proposed solutions are evaluated according to five main criterias such as effectiveness, efficiency, equity, feasibility/implementability, and flexibility/improvability. The research utilized secondary data sources and conducted surveys. The analyses and assessment reveal that in order to increase the low attendance rates in museums of Azerbaijan, government should establish digitalized environment, create interest on visitors and make investments in order to successfully tackle this important issue.
Keywords: Museums -- Attendance; Museums -- Technological innovations; Cultural heritage -- Azerbaijan; Public and International Affairs